سادہ و رنگین تجویدی مصاحف و مخطوطات (قلمی نسخہ جات سے مشینی طباعت تک) کا ارتقاء: Evolution of simple and colorful Tajweedi Qur’an and manuscripts (from handwritten manuscripts to typescripts) - Akhtar, Dr. Qaria Nasreen (Al-Amīr Research Journal for Islamic Studies, 2024)
When the first revelation of the Holy Qur’an was revealed, the institution of the Book of Revelation came into being. The tradition of writing manuscripts in Islamic civilization and civilization was started by the scribes of the Companions, who started writing down the Holy Quran as soon as it was revealed. A written material written by hand on a material object is called a manuscript or a manuscript. A manuscript can be long or short. A pen is usually used to write a manuscript. Which has different forms. These items are used with ink. Since paper was not commonly available at the time of early Islam, calligraphy was done on pieces of bone, membrane, skin, leaves, silk, cloth, metal, paper and wood in the early centuries. Stone and clay tablets and vessels were also used for calligraphy in ancient times. During the rise of Islam, when the paper industry developed in the hands of Muslims, manuscripts were generally written on paper. In modern times, the term manuscript is used for written books. They include many rare and rare manuscripts and common types of manuscripts are also included. In this thesis, samples of manuscripts of the Holy Qur’an are included. Then the letter and color scheme of each pattern is also explained. Lines are also defined by counting lines. Along with the pen copy, a sample of modern Ottoman script is also given so that the reader can read the text of the Surah easily. In this way, manuscripts that describe the calligraphy of different centuries have been analyzed and commented on. Apart from this, the samples of the Qur’anic books of the mechanical era have been explained and commented on so that the public can understand this thesis. Key Words: Qur’an, Manuscript, Calligraphy, Ritual, Typrscript.